Writing in gold: on the aesthetics and ideology of Carolingian chrysography. Issue 1 (2nd January 2023) - Ganz, David
Abstract: Writing in gold has almost completely escaped the attention of art historical manuscript studies. Whereas the semantics and the materiality of gold used in works of goldsmithery as well as in illuminations and panel paintings have been frequently discussed, the fact that gold has been also applied to embellish texts, be they single initials and titles or entire chapters and volumes, has drawn relatively sparse comment. This article is part of a larger research project on Western chrysography. Its scope is to investigate the specific reasons for the use of gold as writing material in the Western Middle Ages. This implies a critical re-evaluation of the standard explanations of the phenomenon in previous research. To approach the issue, it is fruitful to look at single manuscripts and analyse their specific places and ways of application of chrysography. One case that plays a prominent role in this paper is the Golden Psalter from St Gall: an illuminated manuscript that was begun at the court of Charles the Bald and later completed at the monastery of St Gall. In studying this and other examples, the particular and somehow contradictory colour and light effects of chrysography will be emphasized. On the one hand, gold script has the potential to attract visual attention at a long range, especially under the artificial illumination of candlelight; and, on the other, pages with gold script resist a fast, transparent reading of written notation. They draw the reader's attention to the forms and arrangement of the letters, to the weave of the lines, to the oscillation between emphasis and fade-out on the page, and to reflections that dissociate the graphemes from their material carrier, provoking an optical state of suspense. In short, writing in gold constitutes a specific model of ' Schriftbildlichkeit ' or ' Iconographia ', defying the disappearance of the single graphemes behind the text which for a long time has been considered the most characteristic feature of writing.